(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Hypocortisolism or hypoadrenalism is well known as Addison’s disease which is a long term endocrine disorder. In pregnancy it requires much awareness and attention of treating physicians. Early diagnosis, adequate supplement of glucocorticoid and mineralocorticoid and fetal surveillance through regular antenatal checkup is essential for pregnant ladies with Addison’s disease. Patients should be counselled appropriately regarding medication, life-style and precautions to be taken in case of infection, operational exposure or any other stress. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 134-137